1996
DOI: 10.1063/1.117169
|View full text |Cite
|
Sign up to set email alerts
|

Oxynitride films formed by low energy NO+ implantation into silicon

Abstract: A study of low temperature Pd and Ni silicides formed on dry etched silicon surfaces AIP Conf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…The IR peak at 610 cm -1 observed in the SRO monolayer (M20) disappeared for the bilayer (B20) and it could be related to the nitrogen incorporation within the SRO that creates Si-N-O-Si bridges. The presence of these bridges decreased the quantity of strained bonds and Si dangling bonds at the SiO 2 /Si-np interface [45]. The SRN/SRO ilm with Ro = 30 (B30) showed the same IR peaks than the B20 bilayer, except for the 610 cm Figure 3(b)).…”
Section: Silicon-rich Nitride/silicon-rich Oxide (Srn/sro) Bilayermentioning
confidence: 80%
See 2 more Smart Citations
“…The IR peak at 610 cm -1 observed in the SRO monolayer (M20) disappeared for the bilayer (B20) and it could be related to the nitrogen incorporation within the SRO that creates Si-N-O-Si bridges. The presence of these bridges decreased the quantity of strained bonds and Si dangling bonds at the SiO 2 /Si-np interface [45]. The SRN/SRO ilm with Ro = 30 (B30) showed the same IR peaks than the B20 bilayer, except for the 610 cm Figure 3(b)).…”
Section: Silicon-rich Nitride/silicon-rich Oxide (Srn/sro) Bilayermentioning
confidence: 80%
“…It has been reported that this shoulder is less pronounced for the suboxides compared to the stoichiometric oxide [43,44]. The absorption at 610 cm -1 due to unsaturated Si-Si bonds (phonon-phonon interactions) was observed only in M20 (SRO ilm with higher proportion of silicon precursor) showing the presence of structural imperfections at the SiO 2 /silicon nanoparticles (Si-nps) interface [45]. …”
Section: Silicon-rich Oxide (Sro) Ilmmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance peak of Si-N wagging mode near 460 cm -1 is a predominant spectral features [7,8] of silicon oxynitride films. This peak is clearly appeared in oxynitride films at ~462 cm -1 [6,9] while the absorption band assigned at 1080 cm -1 is associated with the Si-O asymmetrical stretching mode [10,11].…”
Section: Results and Discusionmentioning
confidence: 97%
“…The interest in this new class of materials and subsequent research is by analogy with the incorporation of trivalent nitrogen atoms into the silicate network and the obtaining of silicon oxynitride glasses [1][2][3]. Usually the presence of NSi 3 structural units leads to a higher bond density and it is believed that due to this bond density the oxynitride glass network is strengthened in comparison to the original structure.…”
Section: Introductionmentioning
confidence: 99%